Telaah Kritis Aspek Hukum Perjanjian Lisan Jasa Titip Barang - Sri Rumada Sihite (LUTUR Law Journal, 2024)
A jastip business that offers purchases in a place in order to make a profit at each price of goods. Interestingly, this service is without capital because later users of goods delivery services and jastip entrepreneurs agree with the principle of trust. Promote services on social media then wait for orders given by delivery service users. The delivery service business which provides a number of benefits but not infrequently also encounters problems. This is because delivery service business people generally only buy goods after the buyer makes a payment. Different ways of transactions with those in the marketplace or online store that make sellers of goods delivery services have to buy goods first, until the goods arrive at the hands of buyers of goods delivery services. The problem raised by the author in this journal is how the laws and regulations see the rights of jastip users and jastip service providers, how to protect Jastip users against the goods they buy, and what are the legal consequences received by delivery service providers who default on the oral agreement experienced. The results of the study are. Risk is still a burden or borne by the seller who is still the legal owner of the goods, until such time as the goods are legally handed over to the buyer which means ownership has also transferred or moved to the buyer (transper of ownership), by having delivered the goods by the seller to the buyer, then the risk of the goods moving or switching is moving or switching from the seller to the buyer.